The emergence of socioeconomic inequalities in smoking during adolescence and early adulthood - Alves, Joana (2023)
Funding Information: This study received funding from the Foundation for Science and Technology – FCT (Portuguese Ministry of Science, Technology and Higher Education) Unidade de Investigação em Epidemiologia - Instituto de Saúde Publica da Universidade do Porto (EPIUnit) (UIDB/04750/2020). This study is also part of the SILNE-R project, which received funding from the European Commission (EC), Horizon2020 Program, Call PHC6-2014, under Grant Agreement no. 635056. The publication was funded by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020). The funding sources had no role in the study design, collection, analysis or interpretation of the data, writing the manuscript, or the decision to submit the paper for publication. Publisher Copyright: © 2023, The Author(s).